Paraneetroplus synspilus is a Junior Synonym of Paraneetroplus melanurus (Teleostei: Cichlidae) - Mcmahan, Caleb D.; Murray, Christopher M.; Geheber, Aaron D.; Boeckman, Christopher D.; Piller, Kyle R. (Zootaxa, 2011)
The genus Paraneetroplus (Teleostei: Cichlidae) currently consists of 11 species that naturally occur from southern Mexico south to Panama. Paraneetroplus melanurus (Günther 1862) is found in the Lago de Petén system of Guatemala, and P. synspilus (Hubbs 1935) in the Río Grijalva-Usumacinta system, and other systems in Mexico, Belize, and Guatemala. Reported morphological differences between the two nominal species in the literature are vague but center around characteristics of a dark band that begins at the caudal fin and tapers anteriorly near mid-body. This band is reported as straight (horizontal) in P. melanurus but ventrally sloped in P. synspilus. Some authors have previously suggested that these two forms are not distinct. The purpose of this study was to conduct a systematic morphological comparison of P. melanurus and P. synspilus to further investigate their validity. We examined meristic, morphometric, and geometric morphometric characters and failed to recover diagnostic differences between these two forms. The characters proposed to separate them do not allow for their differentiation, and we conclude that P. synspilus is a junior synonym of P. melanurus. A re-description of P. melanurus is provided on the basis of existing type material and additional material recently collected.